Are changes in the dispersion of hours worked a cause of increased earnings inequality? - Daniele Checchi; Cecilia García-Pe\~nalosa; Lara Vivian (IZA Journal of European Labor Studies, 2016)
Earnings are the product of wages and hours of work; hence, the dispersion of hours can magnify or dampen a given distribution of wages. This paper examines how earnings inequality is affected by the dispersion of working hours using data for the USA, the UK, Germany, and France over the period 1989-2012. We find that hours dispersion can account for over a third of earnings inequality in some countries and that its contribution has been growing over time. We interpret the expansion in hours inequality in European countries as being the result of weaker union power that led to less successful bargaining concerning working hours.
Keywords: D31; J22; 330; Earnings inequality; Working hours; Inequality index decomposition